The Conceptualization of Women’s Empowerment by Microlenders in Egypt and its Link to Sustainable Development - Abdellatif, Yasmina (AUC Knowledge Fountain, 2021)
This study examines how microlenders in Egypt conceptualize women’s empowerment and how they see it contributing to achievement of the UN sustainable development goals. Ten Egyptian microlenders were interviewed to understand how they defined and assessed empowerment, the strategies they used to support empowerment, and which sustainable development goals they felt their programs were addressing. Results revealed that, overall, microlenders sought to empower women in economic, social, psychological, and familial ways, and that they used indicators to measure empowerment under each area. They also supported empowerment through mentoring, training and follow-up with their beneficiaries, and by working to include men. In addition, the women in their programs supported the empowerment of other women. Lenders felt that their lending models were not designed to achieve commercial gains but rather the greater good of empowerment and development. They saw the sustainable development goal of gender equality as a primary goal of their programs, but also felt they addressed goals related to poverty and well-being. A need for further qualitative research is recommended to address empowerment from the perspectives of green microlenders as well as the perspective of women borrowers. Keywords: Egypt, women, empowerment, microfinance, microlending, sustainable, development